The development of effector T cell subsets in murine Leishmania major infection - Locksley, R M; Wakil, A E; Corry, D B; Pingel, S; Bix, M; Fowell, D J (Ciba Foundation symposium, 1995)
Leishmania major infection has proven an exceptional model for CD4+ subset development in inbred mice. Most strains contain infection coincident with the appearance of T helper 1 (Th1) cells that produce gamma-interferon (IFN-gamma) required for macrophage activation. In contrast, mice on the BALB background are unable to control infection due to the development of Th2 cells that produce counter-regulatory cytokines, particularly interleukin 4 (IL-4), capable of abrogating the effects of IFN-gamma. Selective gene disruption studies in mice have illustrated critical components of the host response to L. major. Mice deficient in beta 2 microglobulin, which have no major histocompatibility complex (MHC) class I or CD8+ T cells, control infection as well as wild-type mice, whereas mice deficient in MHC class II (and CD4+ T cells) suffer fatal infection. Mice with disruption of the gene coding IFN-gamma are also incapable of containing infection, reflecting absolute requirements for this cytokine. A number of interventions have been demonstrated to abrogate Th2 cell development in BALB mice, enabling these mice to control infection. Each of these--IL-12, anti-IL-4, anti-IL-2, anti-CD4 and CTLA4-Ig--has in common the capacity to make IL-4 rate limiting at the time of CD4+ cell priming.